PENGARUH PENGGUNAAN GEOGEBRA SEBAGAI MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATERI FUNGSI KUADRAT DI KELAS X SMA N 10 MEDAN T.A 2024/2025 - Ceri E Siregar; Samuel Juliardi Sinaga; Ruth M. Simanjuntak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of GeoGebra media on students' learning motivation in quadratic functions. The research method used was quantitative research with a correlational approach. The population was all 10th grade students of SMA N 10 Medan. The instruments used by the researcher were a learning motivation questionnaire and a student ability test. The results showed that the use of GeoGebra as a learning medium had an effect on students' learning motivation. Based on the statistical analysis, the sig (2-tailed) value was 0.008 < 0.05 with a significance level of 5%. This means that α0 is rejected and α is accepted. Based on the results of the simple regression test, the regression equation Y = 77.283 + 0.999X was obtained. Based on the results of the regression significance test, it can be concluded that variable X has a significant effect on Y.